Analysis of Tetrachiral Sandwich Structures at High-Velocity Impact: Influence of the Applied Material and Projectile Core Geometry - Maulana, Sultan; Prabowo, Aditya Rio; Wibowo, Wibowo; Do, Quang Thang; Muttaqie, Teguh; Muhayat, Nurul; Fitri, Siti Nurlita (Salehan Institute of Higher Education, 2024)
This research involved ballistic impact analysis on a tetrachiral sandwich structure in which the shapes of the circular nodes in the tetrachiral core are modified into polygonal shapes, namely a square, hexagon, and octagon. The objectives of this study were to observe the effect of a modified sandwich tetrachiral structure core, investigate the effect of the projectile geometry, and calculate the material performance of the structure. This research was conducted using numerical analysis utilizing the finite element method. The simulation methodology was validated through a benchmarking study, the results of which showed an error below 6%. The findings show that the material with the best performance was Armox 500T, at 5033 J. The most difficult projectile to withstand was conical, followed by ogive, hemispherical, and blunt. The results of the core modification on the tetrachiral sandwich structure show that the octagonal core had better energy absorption, by 2.8%, compared to the circular core. Modifying the node geometry in the tetrachiral core and then analyzing it with stress and strain contours are the novel aspects of this research. Doi: 10.28991/CEJ-2024-010-10-017 Full Text: PDF